Analysis of the Application of Income Tax Article 21 Calculation with an Average Effective Rate based on Government Regulation Number 58 of 2023 at PT XYZ - Dariansyah, Deddy; Rozali, Muhammad (International Humanity Advance, Business & Sciences, 2025)
This study aims to analyze the application of Income Tax Article 21 (PPh Article 21) calculation using the Average Effective Rate (TER) as regulated under Government Regulation Number 58 of 2023, implemented within the corporate environment of PT XYZ. The research uses a quantitative approach with descriptive analysis techniques. Data were collected through literature studies and documentation related to recent tax policies, as well as internal company data concerning the calculation of Article 21 Income Tax. The focus of this research lies in the transition from a progressive tax system to a more simplified, transparent, and practical average effective rate method. The results show that the implementation of the average effective rate simplifies the tax administration process at the company level. Moreover, this approach reduces the potential for errors in calculating and reporting employee income tax, both for permanent and non-permanent employees. The study also found that the implementation of Government Regulation Number 58 of 2023 impacts corporate financial planning, particularly in terms of budgeting for salaries and allowances. This research contributes to practical insights regarding the direct implementation of new tax regulations in the business sector and their implications for compliance and tax efficiency.